Policies and Programs for Sustainable Energy Innovations: Renewable Energy and Energy Efficiency - Daim, T.U (Springer, 2015)
This volume features research and case studies across a variety of industries to showcase technological innovations and policy initiatives designed to promote renewable energy and sustainable economic development. The first section focuses on policies for the adoption of renewable energy technologies, the second section covers the evaluation of energy efficiency programs and the final section provides evaluations of energy technology innovations.